2019
DOI: 10.1063/1.5085865
|View full text |Cite
|
Sign up to set email alerts
|

A novel wide-range microfluidic dilution device for drug screening

Abstract: Microfluidic dilution chip is a crucial approach to perform gradient dilution of experimental samples in many biological investigations. In this study, we developed two serial wide-range dilution chips with dilution rates of 1:1 and 1:4 on the basis of the microfluidic oscillator by designing a series chamber, which was similar to a series circuit. The size of this chamber was adjusted and mixed with the neighboring air chamber to form dilution rates by oscillatory methods. We applied this microfluidic oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, pretreating the channel surface with 75% alcohol and a substance such as Triton X100 can effectively reduce the absorbency [54]. Importantly, this treatment also prevents protein coating on the PDMS surface, which can help to further improve the accuracy of the experiment [55]. In some cases, in addition to these surface modifications, low-temperature curing of PDMS replicas can reduce the number of uncrosslinked free oligomers, which can reduce water absorption [56].…”
Section: Overview Of Microfluidic Systems Utilized As Drug Screening ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pretreating the channel surface with 75% alcohol and a substance such as Triton X100 can effectively reduce the absorbency [54]. Importantly, this treatment also prevents protein coating on the PDMS surface, which can help to further improve the accuracy of the experiment [55]. In some cases, in addition to these surface modifications, low-temperature curing of PDMS replicas can reduce the number of uncrosslinked free oligomers, which can reduce water absorption [56].…”
Section: Overview Of Microfluidic Systems Utilized As Drug Screening ...mentioning
confidence: 99%
“…In addition to these representative examples of C. elegans chip, a more comprehensive set of previous studies can be found in Table 3. Hydrogen peroxide Using the priming valve, the flows were controlled [55] Cu 2+…”
Section: Elegans Chips For Drug Screeningmentioning
confidence: 99%
“…13 In an alternative mechanism, oscillatory microfluidics was used to execute stepwise serial dilution via coordinated operation of pneumatic valves to first meter both the sample and diluent in separate microfluidic chambers and afterwards mix them through oscillatory liquid manipulation. 14 This process was then repeated to prepare a 6-fold dilution series of a hydrogen peroxide solution and study the oxidative stress in C. elegans nematodes. The main drawback of this approach is the need to control each valve individually with an external control unit which makes the device bulky and not compatible with POC applications.…”
Section: Introductionmentioning
confidence: 99%